2020
DOI: 10.1038/s41416-020-01058-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of leukaemias with long-term ambient air pollution exposures in the adult Danish population

Abstract: Background Few population-based epidemiological studies of adults have examined the relationship between air pollution and leukaemias. Methods Using Danish National Cancer Registry data and Danish DEHM-UBM-AirGIS system-modelled air pollution exposures, we examined whether particulate matter (PM2.5), black carbon (BC), nitrogen dioxide (NO2) and ozone (O3) averaged over 1, 5 or 10 years were associated with adult leukaemia in general or by subtype.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
(42 reference statements)
1
6
0
3
Order By: Relevance
“…122 Nonetheless, based on the adult Danish population, the study showed that those who suffered a higher risk of leukemia were exposed to higher concentrations of PM 2.5 prior to diagnosis [OR 1.17 (95%CI: 1.03, 1.32) per 10 μg/m 3 for 10 year average], further study extended this relationship in PM 2.5 components such as black carbon, NH 4 , and NO 3 in the ambient air. 120,121 Jin et al 146 pointed out that PM 2.5 exposure at low doses induced ROS generation which regulated transcription of inflammatory gene, and promoted leukemia progression via the activation of NF-κB and STAT3.…”
Section: Gastrointestinal Cancermentioning
confidence: 99%
“…122 Nonetheless, based on the adult Danish population, the study showed that those who suffered a higher risk of leukemia were exposed to higher concentrations of PM 2.5 prior to diagnosis [OR 1.17 (95%CI: 1.03, 1.32) per 10 μg/m 3 for 10 year average], further study extended this relationship in PM 2.5 components such as black carbon, NH 4 , and NO 3 in the ambient air. 120,121 Jin et al 146 pointed out that PM 2.5 exposure at low doses induced ROS generation which regulated transcription of inflammatory gene, and promoted leukemia progression via the activation of NF-κB and STAT3.…”
Section: Gastrointestinal Cancermentioning
confidence: 99%
“…Compared with coarser atmospheric particulate matter, fine particulate matter has a small particle size and is rich in a large amount of toxic and harmful substances, and it has a long residence time in the atmosphere, so it has a greater impact on human health and atmospheric environmental quality. Researches have shown that the increase in PM2.5 concentration is closely related to the increase in the risk of leukemia in the elderly (Puett et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…En la actualidad, existe suficiente evidencia científica, a través de estudios experimentales en animales y epidemiológicos en humanos, que permite establecer un vínculo causal entre la exposición a contaminantes ambientales y el desarrollo y progresión de enfermedades neoplásicas, especialmente del cáncer de pulmón [53][54][55][56] . Sin embargo, los resultados sobre la relación con otros tipos de tumores han sido menos consistentes [57][58][59][60][61] .…”
Section: Contaminación Y Cáncerunclassified
“…El estudio de la relación de los tumores hematopoyéticos, como las leucemias y los linfomas, con la contaminación ha sido motivo creciente de estudio en los últimos años 57,61 , dada la susceptibilidad de este tipo de tumores a otros agentes externos como los virus o la radiación. A pesar de ello, los resultados no han sido concluyentes.…”
Section: Tumores Hematopoyéticosunclassified
See 1 more Smart Citation